Copper-Catalyzed Construction of Amide Linkages via Coupling between Unactivated Acids and Amines - Rahaman, Ajijur; Bhadra, Sukalyan (Synlett, 2023)
Traditional amide linkage forming reactions by the coupling between an acid and an amine rely primarily on triggering the carboxylic acid counterpart with (over)stoichiometric activating agent(s) and generate unacceptable quantity of nondisposable waste, leading to poor atom economy. Herein, we report an efficient catalytic amide synthesis that proceeds through the in situ activation of the amine counterpart in the form of a reactive N-formyl amine species. The strategy gives an expedient access to an array of structurally varied amides, including dipeptides, from numerous genre of acids and amines without producing stoichiometric solid wastes.
Keywords: copper; N,N-dimethylformamide; amide coupling; radical reaction